2005
DOI: 10.3732/ajb.92.4.744
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of self‐fertilization at geographical range margins? A comparison of demographic, floral, and mating system variables in central vs. peripheral populations ofAquilegia canadensis(Ranunculaceae)

Abstract: Biogeographic models predict that geographically peripheral populations should be smaller, more sparsely distributed, and have a lower per-capita reproductive rate than populations near the center of a species' range. Plants in peripheral populations may, therefore, receive less pollinator visitation and outcross pollination, which may select for self-fertilization to provide reproductive assurance. We tested these predictions by comparing population size, plant density, seed production, floral traits, and mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
135
2
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(152 citation statements)
references
References 72 publications
(88 reference statements)
11
135
2
4
Order By: Relevance
“…Komponen pembungaan terdiri dari fenologi, struktur, dan display perbungaan (Owens et al 1991). Struktur dan display perbungaan mempengaruhi keberhasilan penyerbukan (Herlihy & Eckert 2005;Arroyo et al 2006) dan reproduksi (Wolf et al 2001;Collin & Shykoff 2003;Weber & Kolb 2013;Agullo et al 2015). Fenologi pembungaan, yang meliputi inisiasi, frekuensi, dan durasi pembungaan (Owens et al 1991), merupakan mekanisme alami untuk beradaptasi secara ekologis maupun fisiologis terhadap kondisi lingkungan (Barrett et al 2006;Richardson et al 2013).…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Komponen pembungaan terdiri dari fenologi, struktur, dan display perbungaan (Owens et al 1991). Struktur dan display perbungaan mempengaruhi keberhasilan penyerbukan (Herlihy & Eckert 2005;Arroyo et al 2006) dan reproduksi (Wolf et al 2001;Collin & Shykoff 2003;Weber & Kolb 2013;Agullo et al 2015). Fenologi pembungaan, yang meliputi inisiasi, frekuensi, dan durasi pembungaan (Owens et al 1991), merupakan mekanisme alami untuk beradaptasi secara ekologis maupun fisiologis terhadap kondisi lingkungan (Barrett et al 2006;Richardson et al 2013).…”
Section: Pendahuluanunclassified
“…Fenologi pembungaan, yang meliputi inisiasi, frekuensi, dan durasi pembungaan (Owens et al 1991), merupakan mekanisme alami untuk beradaptasi secara ekologis maupun fisiologis terhadap kondisi lingkungan (Barrett et al 2006;Richardson et al 2013). Variasi fenologi pembungaan berkontribusi pada struktur populasi (Tsaliki & Diekmann 2011;Richardson et al 2013), perilaku agen penyerbuk (Herlihy & Eckert 2005;Arroyo et al 2006), aliran gen (Alizoti et al 2010;Yang et al 2013;Park et al 2014), serta karakter reproduksi (Collin & Shykoff 2003;Alizoti et al 2010;Weber & Kolb 2013;Agullo et al 2015).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…Genetic markers were widely used and, among these, some have conducted by allozyme markers. Many studies reported strong influences of geographical variation on population structures, and its effects on mating systems (Herlihy and Eckert, 2005;Arroyo et al, 2006) and genetic diversity (Rao et al, 2007;Bottin et al, 2007;Dani et al, 2011;Indrioko and Ratnaningrum, 2015). Generally, the small, isolated or fragmented populations might experienced gene flow limitation (Warburton et al, 2000;Craft and Ashley, 2007) and mating systems alteration (Kelleher et al, Ratnaningrum et al 2005; Herlihy and Eckert, 2005;Arroyo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thus changes in the abundance of these pollinator classes could substantially change the selection regime for floral morphology (Castellanos et al, 2003). Furthermore, temporal and spatial variation in pollinator abundances have been found to be substantial and is thus certainly not implausible (for example, Herrera, 1996;Herlihy and Eckert, 2005;Price et al, 2005;Brunet and Sweet, 2006). Changes in pollinator abundance may occur over long time periods owing to a number of factors, including changes in pollinator migration patterns, extinction of pollinators, changes in community composition or adaptation of plants to a new habitat (see Thomson and Wilson, 2008).…”
mentioning
confidence: 99%